Women’s Risk and Needs Assessment (WRNA) in the Czech Republic - Trejbalova, Tereza (Women & criminal justice, 2020)
The focus of practitioners and academics alike has been shifting toward gender-responsive treatment of justice-involved women. One instrument that accounts for the realities of justice-involved women is the Women’s Needs and Risks Assessment (WRNA). In order to inquire about its validity outside the United States, this tool was piloted in the Czech Republic in 2016 with 148 women prisoners. The study examined whether the WRNA is a valid tool for use in the Czech Republic, and how well it predicts the disciplinary infractions of incarcerated women with different cultural backgrounds. Results demonstrated a generalizability of women’s criminogenic needs beyond the United States—several of the gender-neutral (e.g., antisocial friends) and gender-responsive factors (e.g., prior victimization/trauma) that are predictive of American women prisoners’ institutional infractions are also predictive of Czech women prisoners’ infractions. To reduce women’s incarceration rates and to disrupt the intergenerational transmission of crime, we must address women’s criminogenic needs, going beyond traditional male-based risk assessment.